Development of SEFIS Module for Optimizing Children's Quality of Life - Annisa Nur Hikmatus Sholikhah; Astalia Rezky; Farisha Dian Prabaningtyas; Reni Ferida; Aisyah Kamila; Niken Fatimah; Nailul Fauziah (Green Publisher, 2025)
Children’s quality of life, which includes physical, emotional, cognitive, and social aspects, needs early optimization to address various challenge. This study aims to develop a simple physical training module called SEFIS (Sehat Fisik, Psikologis, dan Sosial), designed based on developmental stages to optimize children's quality of life. This study is pilot study using action research approach consisting of assessment, planning, action, and evaluation. The data analysis used was descriptive analysis. Participants consisted of 56 fifth-grade students from a public elementary school. The SEFIS module consists of three main sessions and two ice-breaking activities, including “Befriend Your Emotions”, “Let’s Practice Deep Breathing and Five-Finger Hypnosis,” and “Tong Ball,” along with two ice-breaking sessions: “Cross-Clap” and “Simon Says.” This preliminary study shows that the SEFIS program for elementary school children can help improve their quality of life in physical, psychological, and social aspects. Further research can conduct retesting based on the results of the module evaluation.